Examining the development potential of the masterplan for the V.P. Sysoev "Priamursky" zoo - Sleptsova Olesya A.; Savkova Natalya V. (Архитектон)
We have studied the territory and structure of the zoo located in the suburbs of Khabarovsk on the site of the former children’s summer camp. The main focus is on the analysis of the current layout, problems with the architectural environment, and proposals for re-zoning and renovation. The facility presents a disorganized structure for keeping animals in captivity and requires significant improvements. Visitor profiles have been studied, and possible architectural solutions to increase the commercial attractiveness of the zoo are being examined. A master plan proposal has been developed in cooperation with the V.P.Sysoev Priamursky Zoo, including recommendations how to optimize the use of the territory in order to attract larger audiences and improve animal wellbeing conditions. The study and the project proposal emphasize the importance of an integrated approach to the renovation of the facility in order to achieve scientific and educational goals.